Potential common mechanism of four Chinese patent medicines recommended by diagnosis and treatment protocol for COVID-19 in medical observation period - Wang, Lin; Wang, Zheyi; Yang, Zhihua; Wang, Xingwang; Yan, Liping; Wu, Jianxiong; Liu, Yue; Fu, Baohui; Yang, Hongtao (Frontiers in Medicine, 2022)
This study aimed to explore the common mechanism of action of the four Chinese patent medicine (CPMs) recommended in the Medical Observation Period COVID-19 Diagnostic and Treatment Protocol and to accelerate the new drug development process. Firstly, the active ingredients and targets of the four CPMs were obtained by the Chinese medicine composition database (TCMSP, TCMID) and related literature, and the common action targets of the four TCMs were sorted out. Secondly, the targets of COVID-19 were obtained through the gene-disease database (GeneCards, NCBI). Then the Venn diagram was used to intersect the common drug targets with the disease targets. And GO and KEGG pathway functional enrichment analysis was performed on the intersected targets with the help of the R package. Finally, the results were further validated by molecular docking and molecular dynamics analysis. As a result, a total of 101 common active ingredients and 21 key active ingredients of four CPMs were obtained, including quercetin, luteolin, acacetin, kaempferol, baicalein, naringenin, artemisinin, aloe-emodin, which might be medicinal substances for the treatment of COVID-19. TNF, IL6, IL1B, CXCL8, CCL2, IL2, IL4, ICAM1, and IL10 has been predicted as key targets. 397 GO biological functions and 166 KEGG signaling pathways were obtained. The former was mainly enriched in regulating apoptosis, inflammatory response, and T cell activation. The latter, with 92 entries related to COVID-19, was mainly enriched to signaling pathways such as Coronavirus disease - COVID-19, Cytokine-cytokine receptor interaction, IL-17 signaling pathway, and Toll-like receptor signaling pathway. Molecular docking results showed that 19/21 of key active ingredients exhibited strong binding activity to recognized COVID-19-related targets (3CL of SARS-CoV-2, ACE2, and S protein), even better than one of these four antiviral drugs. Among them, shinflavanone had better affinity to 3CL, ACE2, and S protein of SARS-CoV-2 than these four antiviral drugs. In summary, the four CPMs may play a role in the treatment of COVID-19 by binding flavonoids such as quercetin, luteolin, and acacetin to target proteins such as ACE2, 3CLpro, and S protein and acting on TNF, IL6, IL1B, CXCL8, and other targets to participate in broad-spectrum antiviral, immunomodulatory and inflammatory responses.